Mechanistic features of TiO2-heterogeneous photocatalysis of arsenic and uranyl nitrate in aqueous suspensions studied by the stopped flow technique - Meichtry, Jorge Martin (2015)
The dynamics of transfer of electrons stored in TiO2 nanoparticles to As(III), As(V) and uranyl nitrate in water has been investigated using the stopped flow technique. Suspensions of TiO2 nanoparticles with stored trapped electrons (etrap−) were mixed with solutions of acceptor species to evaluate the reactivity, following the temporal evolution of etrap− by the decrease of the absorbance at 600 nm. The results indicate that As(V) and As(III) cannot be reduced by etrap− under the present conditions. In addition, it was observed that the presence of As(V) and As(III) strongly modified the reaction rate between O2 and etrap−, with an increase of the rate when As(V) was present and a decrease in the presence of As(III). In contrast with the As system, U(VI) was observed to react easily with etrap− and U(IV) formation was observed spectroscopically at 650 nm. The possible competence of U(VI) and NO3− for their reduction by etrap− has been analyzed. The inhibition of the U(VI) photocatalytic reduction by O2 could be attributed to the fast oxidation of U(V) and/or U(IV).